2019
DOI: 10.1111/trf.15523
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two point of care whole blood coagulation analysis devices and conventional coagulation tests as a predicting tool of perioperative bleeding in adult cardiac surgery—a pilot prospective observational study in Japan

Abstract: BACKGROUND It is widely accepted that Point‐of Care Test (PoCT) devices are useful in the detection of coagulopathies in situations of massive bleeding such as major cardiac surgery. These devices contribute to the reduction of blood transfusion. However, their implementation remains limited in Japan because of their cost and lack of health insurance support. STUDY DESIGN AND METHODS Conventional coagulation tests and thromboelastography (TEG)/Sonoclot values were measured in 50 consecutive cardiac surgery cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 42 publications
(76 reference statements)
1
10
0
Order By: Relevance
“…Unfortunately, only a handful of small‐scale observational and perioperative pilot studies have focused on the clinical utility and effectiveness of Sonoclotʼs PF or Quantraʼs PCS measurements in PLT function monitoring. PLT transfusions were found to be associated with postoperative Sonoclot PF measurements in a prospective observational study, which compared TEG to Sonoclot variables in 50 consecutive cardiac surgery patients 62 . It was noted that the degree of correlation diminished after a 20 minutes delay postdraw, suggesting that such a finding would be less useful outside of an immediate POC setting.…”
Section: Clinical Evidence For the Use Of Vet In Evaluating Plt Functionmentioning
confidence: 99%
See 3 more Smart Citations
“…Unfortunately, only a handful of small‐scale observational and perioperative pilot studies have focused on the clinical utility and effectiveness of Sonoclotʼs PF or Quantraʼs PCS measurements in PLT function monitoring. PLT transfusions were found to be associated with postoperative Sonoclot PF measurements in a prospective observational study, which compared TEG to Sonoclot variables in 50 consecutive cardiac surgery patients 62 . It was noted that the degree of correlation diminished after a 20 minutes delay postdraw, suggesting that such a finding would be less useful outside of an immediate POC setting.…”
Section: Clinical Evidence For the Use Of Vet In Evaluating Plt Functionmentioning
confidence: 99%
“…PLT transfusions were found to be associated with postoperative Sonoclot PF measurements in a prospective observational study, which compared TEG to Sonoclot variables in 50 consecutive cardiac surgery patients. 62 It was noted that the degree of correlation diminished after a 20 minutes delay postdraw, suggesting that such a finding would be less useful outside of an immediate POC setting. Early in vitro studies found Sonoclotʼs PF poorly reproducible and highly influenced by PLT counts and modest correlation of the PF to PLT counts was noted in studies.…”
Section: Clinical Evidence For the Use Of Vet In Evaluating Plt Funmentioning
confidence: 99%
See 2 more Smart Citations
“…Terada et al compared the methods of assessing the risk of bleeding after cardiac surgery and the effect of platelet transfusion; the results showed that TEG was better. TEG was originally mainly used to monitor coagulation changes in liver transplantation [ 3 ]. After decades of development, TEG has been widely used in various fields of cardiac surgery [ 4 ], postpartum hemorrhage, hemophilia, and brain trauma surgery [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%